A Study On The Origin Of Zeng Gong’s Historical Discourse And It’s Practice (曾巩史论渊源与实践之研究) - Wong, Hon Yuan (2019)
The customary of historical writing thrives during the Song Dynasty. Both privately compiled history and officially compiled history flourished and thus created a state of contention of different schools. Among those that are more typical in the era of Northern Song Dynasty are the compilation of Taiping Yulan (“Imperial Readings of the TaiPing Era”) led by Li Fang, CefuYuanguiled by Wang Qinruo, New Tang Historical Books and New Five Dynasties Historical Books led by Ouyang Xiu, as well asZizhiTongjianby SimaGuang. All these are historical books that were influential during the same period, and thus shows the people were paying great attention to the history. Therefore, due to the difference in the historical essay’s foothold, historical books that were wrote by different historical writers will derive different historical views and values. The formation of Zeng Gong’s historical essays were situated under such historical background and become a part of many historical essays in that era. Regarding Zeng Gong’s historical essays, it can be noted that the teaching heritage of Zeng family and Ouyang Xiu played important roles in the formation of his historical essays, which can be discovered through his life story, relevant writings and letters with others. Ouyang Xiu, however, has a more impactful guiding effect on the formation and development of Zeng Gong’s historical essay in particular. The reason why Zeng Gong focused his historical essays on the preamble of historical books during his service period at the national archives is also worth researching. This dissertation is based on the comparison of historical background between the 7thyearof QingLi (1047AD), where Zeng Gong first wrote his historical essays, together with the 6th year of Jia You (1061AD) to 2 nd year of Xi Ning (1069AD), which is Zeng Gong’s early service period at national archives. The dissertation also iii uses Zeng Gong’s life story and relevant writings as main clues to investigate the origins of Zeng Gong’s historical essays, in order to outline the overview of the application of his historical essays and its’ specific meaning. Meanwhile, through case study method, the dissertation will also conduct a focused research on Southern Qi Book’s Content Preface, which is Zeng Gong’s most important historical essay, in order to analyse his historical thinking, thereby concluding the formation process and application method of his historical essays.